Implementasi Pembelajaran Projek Kreatif dan Kewirausahaan di Teaching Factory SMK Negeri 9 Padang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the implementation of the Creative Entrepreneurship Project learning program within the Teaching Factory at SMK Negeri 9 Padang. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The research informants consist of PKK teachers, students, and TEFA managers. The findings indicate that the planning of practical activities has been carried out systematically, including the development of a curriculum based on the Merdeka Curriculum using the best learning method, preparation of facilities and infrastructure in accordance with industry standards, procurement of materials through third parties, integrated scheduling systems, and student selection based on skill levels. The implementation of practical activities follows industry work standards, group task division, rotation systems, intensive teacher supervision, an industrial discipline culture, strict quality control, production time efficiency, and both order-based and independent production. Evaluation is conducted comprehensively, covering student competency assessment in four areas (planning, work process, product outcome, and sales), product quality evaluation, learning process evaluation, and the positive economic impact on the school. The implementation of the Teaching Factory has proven effective in developing students’ technical competencies and entrepreneurial spirit, although challenges remain, such as suboptimal TEFA management structure and limited production space.